2002
DOI: 10.1021/jf010537b
|View full text |Cite
|
Sign up to set email alerts
|

Ground Red Peppers:  Capsaicinoids Content, Scoville Scores, and Discrimination by an Electronic Nose

Abstract: High-pressure liquid chromatography (HPLC) was used to determine the capsaicin, dihydrocapsaicin, and total capsaicinoids levels of different ground red pepper samples obtained from local retail markets in Izmir, Turkey. Scoville scores were determined using sensory tests. An electronic nose (EN) was used to discriminate ground red pepper samples by headspace volatiles. EN data were analyzed using discriminant function analysis (DFA). An overall correct classification rate of pepper varieties by EN of 91% was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 12 publications
0
43
0
3
Order By: Relevance
“…44 In previous human studies CAP has been given as red pepper in single meals. However, the content of CAP and pungency differs in the species of Capsicum Annuum L. 45 It is therefore difficult to compare studies unless the pungency is reported in Scoville heat units. Previous studies have shown that addition of approximately 30 mg CAP to meals could increase SNS activity 10,46 and diet induced thermogenesis, 9,47 which is in agreement with the present findings of 2.4% increased RMR with a lower dosage of CAP (1.2 mg).…”
Section: Discussionmentioning
confidence: 99%
“…44 In previous human studies CAP has been given as red pepper in single meals. However, the content of CAP and pungency differs in the species of Capsicum Annuum L. 45 It is therefore difficult to compare studies unless the pungency is reported in Scoville heat units. Previous studies have shown that addition of approximately 30 mg CAP to meals could increase SNS activity 10,46 and diet induced thermogenesis, 9,47 which is in agreement with the present findings of 2.4% increased RMR with a lower dosage of CAP (1.2 mg).…”
Section: Discussionmentioning
confidence: 99%
“…Many different techniques have been employed for the extraction of capsaicinoids from pepper, such as maceration [11], magnetic stirring [12], enzymatic extraction [13], ultrasound-assisted extraction [14], Soxhlet [15], extraction by supercritical fluids [16], extraction by pressurized liquids [17] and microwave-assisted extraction [18,19]. The conventional extraction methods, like Soxhlet extraction, which have been employed for decades, need long extraction times and require relatively large quantities of solvent [20].…”
Section: E-mail Address: Miguelpalma@ucaes (M Palma)mentioning
confidence: 99%
“…To evaluate the effect of the volume of the solvent on the extraction, a series of extractions were carried out with different volumes of solvent (15,25,40 and 50 mL). The rest of the extraction conditions were: temperature of 50 • C, approximately 1 g of sample, 10 min of extraction and methanol as solvent.…”
Section: Volume Of Solventmentioning
confidence: 99%
“…Many techniques for the extraction of capsaicinoids from peppers have been studied, such as maceration [9], magnetic stirring [10], Soxhlet [11,12], ultrasound-assisted extraction [13], extraction by means of supercritical fluids [14], extraction by pressurized liquids [15] and enzymatic extraction [16]. These techniques are employed in response to the increasing demand for methods that allow the extraction process to be automated, extraction times to be shortened, the consumption of solvents to be reduced, and the exposure of operative personnel to solvents to be minimised.…”
Section: E-mail Address: Miguelpalma@ucaes (M Palma)mentioning
confidence: 99%